Lincoln in the bardo [compact disc, unabridged] - Saunders, George, 1958- (Random House Audio ; Books on Tape, 2017)
Traces a night of solitary mourning and reflection as experienced by the sixteenth president after the death of his eleven-year-old son at the dawn of the Civil War.